INNOVATION, CREATIVE DESTRUCTION, AND SUSTAINABLE GOVERNANCE: THEORETICAL PERSPECTIVES AND PATHWAYS TOWARD COP30 - de Souza Freire, Fátima; Madeira Nogueira, Jorge; Daroit, Doriana (RP3 - Revista de Pesquisa em Políticas Públicas, 2025)
Abstract The awarding of the 2025 Nobel Prize in Economics to Philippe Aghion, Peter Howitt, and Joel Mokyr enshrined one of the most transformative paradigms in contemporary economic thought: that sustained growth arises from cycles of innovation that destroy old structures and create new forms of productivity, value, and social organization. Originally formulated in the early 1990s and further developed in subsequent decades, this theory now offers a decisive interpretive framework for understanding the challenges of ecological transition, innovative public policies, and global governance oriented toward sustainability.